Synchronizing estrus in replacement beef heifers using select synch, MGA, AND PGF2 - G.C. Lamb; J.A. Cartmill; B.A. Hensley; S. El-Zarkouny; J.S. Heldt; T.J. Marple; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1999)
The Select Synch protocol (GnRH at day - 7, PGF2 at day 0, AI at detected heat) was compared to protocols using either MGA + prostaglandin (Colorado system) or two injections of prostaglandin to synchronize estrus in replacement heifers at three locations. Percentage of heifers detected in heat before, during, or after the target breeding week was not different among treatments but varied in percentages among locations. Overall conception rates ranged from 64 to 69%. Pregnancy rates varied from 46 to 56% and tended to be greatest in the MGA + PGF2" treatment. Costs of these treatments ranged from $3.50 to $8 and were lowest for the MGA + PGF2 protocol.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Heifers; Estrus-synchronization; GnRH; PGF2; AI